Accelerated bone defect closure after administration of nano bovine hydroxyapatite-calcium sulfate-gelatin scaffold in bone defect models - Pratama, Yusuf Alif; Ananta, Ita Pramudia; Haris, Muhammad Shofwan; Maghfiroh, Nuril; Nabila, Hawin; Ardianto, Chrismawan; Rahmadi, Mahardian; Khotib, Junaidi; Hendradi, Esti; Bakhtiar, M. Taher; Mazidda, Sakinato; Budiatin, Aniek Setiya (JPPRes, Antofagasta, Chile, 2025)
Context: Bone defects associated with fractures exceeding 2 cm in circumference present significant clinical challenges due to the high risk of nonunion or malunion. Scaffold implantation offers a non-toxic, effective strategy to support bone regeneration and restore structural integrity. Aims: To evaluate and compare the regenerative effects of bovine hydroxyapatite-calcium sulfate-gelatin (BHA-CS-gelatin) and nano-BHA-CS-gelatin scaffolds. Focus was placed on cellular morphology, including osteoblasts, osteocytes, and osteoclasts, cell migration, and the expression of osteogenic markers: collagen type I (COL1), Runx2, osteocalcin, and osteoprotegerin (OPG). Methods: In vivo experiments used New Zealand White rabbits with surgically induced bone defects treated with either BHA-CS-gelatin or nano-BHA-CS- gelatin scaffolds. Bone regeneration was assessed by histological, immunohistochemical, and ELISA analyses. Rabbits were sacrificed on days 7 and 28 for histology and immunohistochemistry evaluations. OPG levels were measured by ELISA on days 0, 1, 3, 5, 7, 14, and 28. Results: Histological analysis showed enhanced migration of osteoblasts, osteocytes, and osteoclasts in the nano-BHA-CS-gelatin group. Immunohistochemistry revealed significantly higher expression of COL1, Runx2, and osteocalcin in this group at day 28 (p<0.05). ELISA demonstrated a significant increase in OPG levels on day 14 compared with the conventional BHA-CS-gelatin scaffold group (p<0.05). Conclusions: Nano-BHA-CS-gelatin scaffolds significantly accelerate bone defect closure and enhance osteogenic marker expression more effectively than conventional scaffolds. These results support their preclinical potential application in bone repair and regenerative medicine. Keywords: bone; bone remodelling; calcium sulfate; nano bovine hydroxyapatite; noncommunicable diseases; scaffold.